Role of LATS1/2 in Prognosis of Advanced Gastric Cancer and Its Relationship With the Tumor Immune Microenvironment - Guo, Yixian; Liu, Xu; Xu, Danhua; Huang, Chen; Wang, Zeyu; Xia, Xiang; Zhu, Chunchao; Xu, Jia; Zhang, Zizhen; Shen, Yanying; Zhao, Wenyi; Zhao, Gang (Frontiers in Oncology, 2020)
Background: Gastric cancer (GC) remains a refractory cancer, particularly in Eastern Asia. Large tumor suppressor kinases 1/2 (LATS1/2) are core members of the Hippo pathway. The role of LATS1/2 in the prognosis of different subtypes of advanced gastric cancer and its relationship with the tumor immune microenvironment in GC remain unknown. Exploring the role of LATS1/2 in GC might provide potential immunotherapeutic approaches for treating GC. Methods: Four hundred and ninety surgically resected primary GC samples were assessed for LATS1/2, CD8, FOXP3 and CD163. Correlations between LATS1/2 expression and immune-related markers were investigated, and the prognoses of patients with different GC subtypes were analyzed. Results: CD8 and CD163 appeared to be favorable and adverse prognostic factors, respectively. LATS1/2 and FOXP3 did not predict patients’ overall survival. However, in microsatellite-stable GC patients, high LATS1/2 and FOXP3 expression and low CD8 expression predicted poor prognoses. Furthermore, high LATS1/2 expression was significantly correlated with decreased CD8 and increased FOXP3. Combined analysis of LATS1/2, CD8 and FOXP3 had better prognostic accuracy than did each marker individually. Conclusions: Different biological molecules can predict the prognoses of different types of GC patients. LATS1/2, core kinases in the Hippo pathway, are closely related to CD8 and FOXP3. Further understanding the mechanisms of LATS1/2 in CD8+ T cells and FOXP3+ Treg cells provides further theoretical basis and potential targets for GC immunotherapy.